The Formation of the Concept of Smart Sustainable City with the Purpose of Environmental Protection - BALOVA, Suzana L.; García de VELAZCO, Judith J. Hernández; POLOZHENTSEVA, Irina V.; CHERNAVSKY, Mikhail Yurjevich; SHUBTSOVA, Lyudmila Vladimirovna (Journal of Environmental Management and Tourism, 2021)
The article is aimed at identifying the main areas of a smart sustainable city formation that can help to protect the environment. The article presents the results and definitions of a smart city and its variant, a smart sustainable city. Based on an expert survey, the main areas of a smart sustainable city formation have been identified, some measures recommended for implementation in these areas have been formulated, and examples of their implementation in international practice have been presented.